KESALAHAN BERBAHASA INDONESIA MAHASISWA ASING DALAM MEDIA KOMUNIKASI WHATSAPP - Sadiyah, Mutiara Halimatu’s; Khotimah, Pebriliana Husnul; Khaerunnisa, Khaerunnisa (Prosiding Seminar Nasional Bahasa Ibu, 2025)
Analyzing language errors in foreign student communication on Whatsapp communication media. This study is a descriptive study, namely describing new words and phrases acquired by foreign Indonesian language learners (BIPA) at the Muhammadiyah University of Jakarta. In learning the use of Indonesian, BIPA learners often experience sentence errors in communicating both orally and in writing. This study began with a pre-study conducted in December 2024 at the Faculty of Islamic Studies, Muhammadiyah University of Jakarta. During the pre-study, foreign students were interviewed directly about language acquisition when entering the class and their experience of communicating with native Indonesian speakers via the Whatsapp social media. From the discussion that has been presented, it can be seen that there are more errors at the syntactic level than at the phonological level. This happens because in the process of learning Indonesian, learners need time to master language usage skills. Inaccuracy in writing sentences is the most common mistake made by learners. So that the meaning captured by the interlocutor is not quite right. Furthermore, some phrases that should appear in the sentence. Finally, errors in writing sentence structures are not quite right, so they have an ambiguous meaning.